Réponses

2014-09-06T15:11:56+02:00
2/3 × 9/5 - 1/4
= 18/15 - 1/4
= 18 x 4 / 15 x 4 - 1 x 15 / 4 x 15
= 72/60 - 15/60
= 57/60
= 3 x 19 / 3 x 20
= 19/20

(4/5 - 2) × (3/4 - 2/3)
= (4/5 - 2 x 5 / 1 x 5) x (3 x 3 / 4 x 3 - 2 x 4 / 3 x 4)
= (4/5 - 10/5) x (9/12 - 8/12)
= - 6/5 x 1/12
= - 6/60
= 6 x - 1 / 6 x 10
= - 1/10

(2/5 + 1/3) ÷ 2/3
= (2 x 3 / 5 x 3 + 1 x 5 / 3 x 5) : 2/3
= (6/15 + 5/15) : 2/3
= 11/15 x 3/2
= 33/30
= 3 x 11 / 3 x 10
= 11/10

16/15 ÷ 2/9 - 2/3
= 16/15 x 9/2 - 2/3
= 144/30 - 2/3
= 144/30 - 2 x 10 / 3 x 10
= 144/30 - 20/30
= 124/30
= 2 x 62 / 2 x 15
= 62/15

2/13 - 5/13 ÷ 10/16
= 2/13 - 5/13 x 16/10
= 2/13 - 80/130
= 2 x 10 / 13 x 10 - 80/130
= 20/130 - 80/130
= 60/130
= 10 x 6 / 10 x 13
= 6/13